Police incentives and weak institutions : evidence from Bogotá (2019)
This paper studies how the presence of weak institutions on the Criminal Justice System (CJS), measured in terms of a low institutional offer, impacts police productivity in Bogotá. The main results indicate that a poor institutional offer produces low incentives on police officers to arrest criminals, which affects the certainty of punishment for criminals when committing a crime and may produce a criminogenic effect. As an additional exercise, I apply an optimal location model proposed by Church (1999) to enhance crime deterrence via increasing the certainty of punishment, by optimally allocating CJS equipment according to the crime dynamics of the city and increasing the incentives of police officers to arrest a criminal.